Hubungan Self Efficacy (Efikasi Diri) Dan Motivasi Belajar Dengan Prestasi Belajar Siswa Kelas IV SDN Gugus III Kecamatan Labuhan Haji - Hidyatul Fatmi; Asrin; Iva Nurmawanti (Mataram University, 2024)
The low learning achievement of students is caused byself-efficacyand learning motivation, which is one of the psychological factors that influences learning achievement and acts as a motivator to achieve good performance. This research aims to see the relationship between self-efficacy and learning motivation and the learning achievement of class IV students at SDN Cluster III, Labuhan Haji sub-district. The type of research used is correlational research. The population of this research is all class IV students at SDN Gugus II, Labuhan Haji District and the research sample is 60 students. Research data was collected through questionnaires to measure students' self-efficacy and learning motivation and documentation for student achievement. Data analysis techniques use prerequisite tests (linearity test data normality) and hypothesis testingproduct moment correlationat a significance level of 5%. The research results show that 1) There is a positive and significant relationship between self-efficacy and learning achievement, where the value obtained is rcount (3.715) > rtable (0.254) with a sig.(2-tailed) of 0.000 <0.05. 2)The existence of a positive relationship between learning motivation and learning achievement is proven by the value of rcount (4.647)> rtable (0.254) with sig.(2-tailed) of 0.000 <0.05. 3) There is a positive and significant relationship between self-efficacy and learning motivation and learning achievementvalue is obtained sig.(F.change) of 0.000 < 0.05, is at a strong relationship level. The magnitude of the contribution or contribution of self-efficacy and learning motivation to learning achievement was 52.6% with 47.4% influenced by other factors not included in the research.